Management of blast disease of finger millet ( Eleusine coracana) in mid-western Himalayas - Kumar, Bijender (Indian Phytopathology, 2011)
Blast of finger millet caused by Pyricularia grisea (Cke.) Sacc. is serious disease of finger millet and causes considerable reduction in yield. In order to manage this disease, the experiments were carried out at G. B. Pant University of Agriculture and Technology, Hill Campus, Ranichauri. Results revealed that five finger millet genotypes viz; OEB 259, VL 340, PRM 9809, HR 374, and VL 149 were completely free from blast disease. Seed treatment with Pseudomonas fluorescens strain 551 (Pf 1) @ 6 and 10 gm kg-1 seed, respectively followed by two sprays of Pf 1 @ 0.6% first at the time of 50 percent ear head emergence and second ten days later, were best in terms of disease control, increasing grain yield and percent avoidable loss. The treatments were also found economical in managing the blast disease.